CULTIVATION OF MICROALGAE FOR BIO OIL PRODUCTION AND CARBON DIOXIDE REMOVAL - Aliah, Muhammad Hidayat (Universiti Teknologi Petronas, 2010)
The use of fossil fuel is now widely accepted as unsustainable due to depleting resource and the accumulation of greenhouse gases in the environment that have already exceeded the dangerously high threshold of 450ppm COre. To achieve environmental and economic sustainability, fuel production processes are required not only renewable but also capable of sequestering atmospheric COz. Microalgae are a versatile field due to its wide range of application and industries. It has been investigated that microalgae can be used for the production of a number of products ranging from fuel, pharmaceutical, food and health. In the fields of fuel and energy only microalgae can be used to produce biodiesel, bio-oil, bio-syngas and biohydrogen. Not limited by that, the production of microalgae can be couple with C02 mitigation and wastewater treatment. Development in microalgae cultivation and downstream processes are expected to further enhance cost effectiveness of the biofuel from microalgae. This research entitled "Cultivation of microalgae for biooil production and C02 removal" is done to investigate and to develop a microalgae cultivation system with the aim to improve the C02 removal and fixation during the cultivation of microalgae. The main objective of this research is to study on the cultivation technique(s) of microalgae specifically bioreactor, the C02 utilization of the system, potential species of microalgae system for both bio-oil production and C02 removal system as well as the optimum growth condition for cultivation of microalgae. The scope of study will be narrowed down to the growth rate and survival of microalgae species, utilization of wild algae for the mentioned purposes, the use of microalgae as biomass, the different technique for the production of microalgae and the C02 utilization technique using monoculture as well as mix-culture.